Independensi Aparat Pengawas Intern Pemerintah Guna Pelaksanaan Good Governance Berbasis CACM Di Lingkungan Pemerintah Daerah - Herlin Angela Dewi (Arena Hukum, 2022)
This study aims to determine the independence of the government internal supervisory apparatus in order to realize the implementation of good governance in the Continuous Auditing and Continuous Monitoring (CACM) based local government environment. This normative juridical research show that CACM are tools that are expected to support the implementation of audits in order to produce effective and efficient audits. The research method used is normative juridicial. The results showed that APIP maintain independence and responsibility for supervision and guidance and be free from pressure from any party in order to realize reliable supervisory results the implementation of good governance in local government based on CACM.